Pengembangan Desain Alat Pemotongan Kripik Singkong Dalam Peningkatan Produksi (Studi Kasus Pada UMKM di Pemalang) - Saputro, Yoyo; Yudha Saksono, Deky (Accurate: Journal of Mechanical Engineering and Science, 2021)
Cassava is a tuber plant that can grow in tropical areas with hot and humid climates. In tropical climates cassava is needed for its growth process so that this plant cannot grow at temperatures below 10 c. Cassava is a tuber or tree root that can grow on sandy to clay soil, as well as on low fertility soil. The length of cassava ranges from 15-30 cm with a relatively different diameter, which is 2-5 cm. Cassava has a skin consisting of two layers, the first layer is the outer skin while the second layer is the inner skin with white or yellowish flesh. In its production so far, cassava cutting is still using human power (manual). It would be better if the production of cassava cutting increased without ignoring the existing human aspects. Therefore, a machine is needed as a human tool in increasing the productivity of cassava cutting. Significant results or not, can later be observed from the data obtained before and after using the machine. A significant increase after the experiment was carried out means that the cassava cutting machine was able to help the existing cutting process. This can be seen later by using SPSS calculations.